Meningkatkan prestasi sekolah melalui manajemen PARKOSI (partisipasi, kolaborasi, dan eksekusi) di SD negeri 1 semarapura klod - Ni Made Astiti (Indonesian Journal of Educational Development, 2021)
This best practice is the result of a work done at SD Negeri 1 Semarapura Klod. The principal is the main figure in improving the quality and development of the school. The purpose of this paper is to provide an overview of: 1) PARKOSI management steps, and 2) the results or impacts of implementing PARKOSI's management program. The stages in implementing PARKOSI management developed at SD Negeri 1 Semarapura Klod consist of (1) forming a team work, (2) implementing PARKOSI management, and (3) partnership. The results of the implementation of PARKOSI management are: (1) it can increase participation, collaboration and execution between the principal and the teacher, the teacher and the teacher, the teacher and the students, the school with the school committee and the parents of students; (2) the achievement of schools has increased both at the sub-district and district levels; and (3) there is a partnership program between parents, committees, community members and other institutions. The impact of the implementation of PARKOSI management, namely: (1) increased participation and collaboration of principals, teachers and staff in efforts to increase school achievement; (2) students have responsibility and get motivation to improve achievement; and (3) parents believe in the school. Based on this experience, it is recommended that the principal (1) condition school activities through PARKOSI management; and (2) make careful planning for improving school achievement. Best practice ini merupakan hasil karya yang dilakukan di SD Negeri 1 Semarapura Klod. Kepala sekolah merupakan tokoh utama dalam peningkatan mutu dan pengembangan sekolah. Tujuan karya tulis ini adalah untuk memberikan gambaran mengenai: 1) langkah-langkah manajemen PARKOSI, dan 2) hasil atau dampak dari pelaksanaan program manajemen PARKOSI. Tahapan dalam implementasi manajemen PARKOSI yang dikembangkan di SD Negeri 1 Semarapura klod terdiri atas (1) pembentukan team work, (2) pelaksanaan manajemen PARKOSI, dan (3) kemitraan. Hasil dari Implementasi manajemen PARKOSI yaitu: (1) dapat meningkatkan partisipasi, kolaborasi dan eksekusi antara kepala sekolah dengan guru, guru dengan guru, guru dengan siswa, pihak sekolah dengan komite sekolah dan orang tua siswa; (2) meningkatnya prestasi yang diraih sekolah baik ditingkat kecamatan maupun di kabupaten; dan (3) terjalin program kemitraan antar orang tua, komite, masyarakat sekotar dan lembaga lain. Dampak dari implementasi manajemen PARKOSI yaitu: (1) meningkatnya partisipasi dan kolaborasi kepala sekolah, guru dan staf dalam upaya peningkatan prestasi sekolah; (2) peserta didik memiliki tanggung jawab dan mendapat motivasi untuk meningkatkan prestasi; dan (3) orang tua percaya kepada sekolah. Berdasarkan pengalaman ini direkomendasikan agar Kepala sekolah (1) mengkondisikan kegiatan sekolah melalui manajemen PARKOSI; dan (2) membuat perencanaan peningkatan prestasi sekolah secara cermat.